2015
DOI: 10.1017/s1751731114003127
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and activity levels as predictors of calving for dairy cows

Abstract: The Australian dairy herd size has doubled over the last 20 years substantially increasing the time that farmers require for individual animal attention to monitor and intervene with events such as calving. Technology will help focus this limited labour resource on individual cows that require assistance. The objective of this experiment was to first determine the profiles of rumination duration and level of activity as determined by sensors between, and within, days around calving and second to use these data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
9
29
2
1
Order By: Relevance
“…A decrease in "rumination" prior to calving was observed in this study, consistent with other studies (Bar and Solomon, 2010, Bucher and Sundrum, 2014, Clark, et al, 2015, Ouellet, et al, 2016, Pahl, et al, Saint-Dizier and Chastant-Maillard, 2015, Schirmann, et al, 2013). In the current study, this decrease was about 15 minutes per hour (the difference between the case and control dataset during the hour in which calving started).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A decrease in "rumination" prior to calving was observed in this study, consistent with other studies (Bar and Solomon, 2010, Bucher and Sundrum, 2014, Clark, et al, 2015, Ouellet, et al, 2016, Pahl, et al, Saint-Dizier and Chastant-Maillard, 2015, Schirmann, et al, 2013). In the current study, this decrease was about 15 minutes per hour (the difference between the case and control dataset during the hour in which calving started).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have observed changes in feeding and resting behaviour determined by sensors in the last 24 hours before calving (Bucher and Sundrum, 2014, Clark, et al, 2015, Schirmann, et al, 2013, Titler, et al, 2015. No such effects were observed in the data of the sensor parameters "feeding" and "not active" in the current study.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations